2013
DOI: 10.3892/mmr.2013.1796
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of human hair follicle stem cells into endothelial cells induced by vascular endothelial and basic fibroblast growth factors

Abstract: Hair follicle stem cells (HFSCs) possess powerful expansion and multi‑differentiation potential, properties that place them at the forefront of the field of tissue engineering and stem cell‑based therapy. The aim of the present study was to investigate the differentiation of human HFSCs (hHFSCs) into cells of an endothelial lineage. hHFSCs were expanded to the second passage in vitro and then induced by the addition of vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF) to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 55 publications
2
22
0
Order By: Relevance
“…Nevertheless, some stained blood vessels in brown color were observed in the PBS group. Consistent with these finding, recent studies have confirmed that creation and development of new vessels during the early wound healing process enhanced [7,9,14] , possibly due to the presence of stem cells. These newly vessels could decrease the inflammation phase and provide the nutrients and oxygen for cell proliferation and tissue regeneration [7,9,14] .…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Nevertheless, some stained blood vessels in brown color were observed in the PBS group. Consistent with these finding, recent studies have confirmed that creation and development of new vessels during the early wound healing process enhanced [7,9,14] , possibly due to the presence of stem cells. These newly vessels could decrease the inflammation phase and provide the nutrients and oxygen for cell proliferation and tissue regeneration [7,9,14] .…”
Section: Discussionsupporting
confidence: 71%
“…Consistent with these finding, recent studies have confirmed that creation and development of new vessels during the early wound healing process enhanced [7,9,14] , possibly due to the presence of stem cells. These newly vessels could decrease the inflammation phase and provide the nutrients and oxygen for cell proliferation and tissue regeneration [7,9,14] . Angiogenesis activity of HFSCs and improved overall wound healing process have also been reported in Heidari et al [9] and Xu et al [14] studies.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Occludin is one of the main components of TJs in the majority of tissues (30), while claudin-5 is only expressed in GEnCs in the kidney (31). The two proteins are critical in maintaining the endothelial barrier (32)(33)(34); therefore, the expression of occludin and claudin-5 was examined following exposure to AGEs in the presence or absence of BiPS. Immunoblotting analysis suggested that AGEs reduced the total cellular content of occludin and claudin-5, likely due to protein degradation, while expression levels in the cultures co-treated with AGEs and the MMP-2/9 inhibitor BiPS were not different from those in the untreated control cultures, again indicating that AGEs reduced the expression of occludin and claudin-5 by increasing MMP-2/9-mediated proteolysis.…”
Section: Discussionmentioning
confidence: 99%